When motherhood beckons : an exploration of the transition to motherhood for HIV positive women : a thesis presented in partial fulfillment of the requirements for the degree of Masters in Philosophy, Massey University, Manawatu, New Zealand - Hinks, Amanda (Massey University, 2010)
The aim of the research was to explore the transition to motherhood for women who have been diagnosed with HIV before pregnancy.Pregnancy is a time of adjustments for all women; socially psychologically and physically, the midwife has a fundamental role in supporting the woman to make a successful transition. HIV is increasing in New Zealand’s heterosexual population and with the national introduction of antenatal HIV testing midwives the diagnoses made will increase. Communities and health professionals need to hear about women’s experiences and recommendations from research about how best to provide individualised care for both mother and baby. This small research study was undertaken in 2008.Three women living in New Zealand with a positive HIV diagnosis were interviewed about their transition to motherhood. The babies of mothers in this study were aged between 3 and 18 months and the women knew their HIV diagnosis prior to pregnancy. The women spoke candidly about their experience of becoming pregnant, being pregnant and the transition to motherhood over the subsequent months of their babies’ lives. Three chapters present the themes from the women’s narratives; Chapter Four details the journey to becoming a mother. The themes identified were the desire to become a mother; “working hard for this baby”; maternal-infant attachment and “becoming a mother changes everything.” The themes in Chapter Five focus on how the women manage stigma and disclosure of their condition. The theme of managing disclosure in their personal world to family, friends and the child is identified. The maintenance of privacy and confidentiality is a theme arising from their step into the health service. In Chapter Six the theme of disempowering behaviours and perceived lack of evidence based care is discussed. The women describe how knowledge of HIV positive mothers was lacking as some health professionals queried “why aren’t you breastfeeding?” The women identified sources of support and knowledge which used to address the imbalance of power they felt whilst engaging with health professionals and wider society. In conjunction with midwives and other health professionals, the communities in which the women live are an integral component of supporting women to become mothers.
Keywords: HIV-positive women; HIV infections; Motherhood; Pregnancy; Childbirth; Attitudes; New Zealand